Enhancing Transitions From Rehabilitation Patient to Wellness Participant for People With Disabilities: An Opportunity for Hospital Community Benefit - Carroll, Nathan W.; Hall, Allyson G.; Feldman, Sue; Thirumalai, Mohanraj; Wade, Jamie Tinker; Rimmer, James H. (Frontiers in Public Health, 2020)
Pressure is increasing on not-for-profit hospitals to demonstrate that they provide sufficient benefit to the community to justify their tax-exempt status. Many industry observers have suggested that this community benefit should address unmet medical needs within the community, deficits in the social determinants of health, or health disparities within communities. We argue that one area of clear unmet need is assistance in helping bridge the transition that people with disabilities (PWD) must make from rehabilitation patient to wellness participant. Programs to bridge this transition are necessary because many PWD struggle to identify strategies to maintain and maximize their own well-being after discharge from the healthcare system. As a result, PWD have worse health outcomes than non-disabled individuals. To address these needs, we propose hospitals take a leading role in establishing new, community-based efforts to provide PWD with benefits that will support their effort to self-manage health. Hospitals are well-suited to lead the creation of these programs because of the important role they play in providing services to PWD and because of their ability to bring together multiple stakeholders required to make supportive programs sustainable.